Whole-genome sequencing-based characterization of Salmonella enterica Serovar Enteritidis and Kentucky isolated from laying hens in northwest of Iran, 2022–2023 - Vakili, Shirin; Haeili, Mehri; Feizi, Adel; Moghaddasi, Kiarash; Omrani, Maryam; Ghodousi, Arash; Cirillo, Daniela Maria (Gut pathogens, 2025)
Background The transmission of Salmonella spp. to human through the consumption of contaminated food products of animal origin, mainly poultry is a significant global public health concern. The emerging multidrug resistant (MDR) clones of non-typhoidal Salmonella (NTS) serovars, have spread rapidly worldwide both in humans and in the food chain. In this study NTS strains were isolated from diseased laying hens in Iran and were further studied by whole-genome sequencing (WGS) to investigate the prevalent serovars, multilocus sequence types, antimicrobial resistance and virulence genes. Results Out of eight isolated Salmonella spp. six were identified as S . Enteritidis serovar ST11 (n = 5) or ST5824 (n = 1), and two isolates were recognized as S. Kentucky serotype ST198 lineages. The aminoglycoside resistance gene aac(6′)-Iaa was the most frequently detected gene being present in all serovars, but it did not confer phenotypic resistance to corresponding agents (tobramycin and amikacin). All S. Enteritidis isolates carried a single GyrA D87N/Y substitution. Other identified antimicrobial resistance genes (ARGs) including tetA , floR , sul1 , dfrA1, aph(3′)-Ia and double gyrA and parC mutations conferring high-level ciprofloxacin resistance (CIP R ) (MIC ≥ 16mg/L) were only found in S . Kentucky isolates. The comparison of phenotypic and genotypic antimicrobial resistance (AMR) profiles revealed inconsistent results for some antibiotics. A total of 11 different Salmonella Pathogenicity Islands (SPIs) including SPIs-1, to 5, 9, 10, 13, 14, C63PI, CS54 and several virulence genes related to type III secretion system, adhesins, iron and magnesium uptake, serum and antimicrobial peptide resistance were detected among the isolates. Conclusions Our study reports emergence of a highly MDR- CIP R S . Kentucky ST198 clone form poultry associated sources in Iran. The presence of numerous virulence determinants, SPIs and ARGs in the examined NTS isolates poses a significant risk for food safety. The inconsistencies between the genotypic and phenotypic AMR profiles indicate that WGS data alone may not be always sufficient for guiding therapeutic strategies.